Media Audio Visual Sebagai Inovasi Pembelajaran Bahasa Inggris di Mi Tahfidz As Sholihah Bawen, Semarang - Al Wiyah, Naili Amani; Umami, Maslihatul (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to describe the application of audio visual media as an innovation in learning English at MI Tahfidz As Sholihah. Data was gathered through teacher and student observation, interviews, and documentation using a descriptive qualitative methodology. The findings demonstrated that students active engagement in the learning process, vocabulary comprehension, and motivation to study were all improved by the use of audio-visual materials including interactive audio and animated films. This media also helps to create a more interesting and contextualized learning atmosphere, although there are still technical constraints such as device limitations. Overall, audio-visual media is considered effective and relevant as an innovative learning strategy that suits the characteristics of students in a tahfidz-based madrasah environment. Keywords: Audio-Visual Media, Learning Innovation, English Language, MI Tahfidz As Sholihah